Upaya Peningkatan Media Wordwall terhadap Motivasi Belajar pada Pelajaran SKI Materi Kisah Teladan Nabi Muhammad SAW Kelas V MI Islamiyyah Kraksaan - Alfina Muniffatuz Zahra’; Ainur Rofiq Sofa (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to examine the impact of utilizing the Wordwall interactive media on student motivation in learning Islamic Cultural History (SKI), focusing on the exemplary stories of Prophet Muhammad SAW for Grade V students at MI Islamiyyah Kraksaan. This research employs a quantitative experimental approach with a pretest-posttest design involving 25 students as participants. The results reveal that the application of Wordwall significantly enhances student motivation, with a 20% average increase in pretest-posttest scores. Observations show heightened student engagement during lessons, marked by active participation in discussions, asking questions, and completing tasks. Additionally, Wordwall facilitates better understanding and retention of moral values exemplified by Prophet Muhammad SAW, such as honesty, patience, and compassion. Challenges include the necessity of stable internet access and device availability. This study underscores Wordwall's potential as an effective educational tool to create a more interactive, enjoyable, and meaningful learning experience.